Study on Business Opportunities Extracted From E-Waste a Review - N. Gomathi, Dr; P L, Rupesh (International Journal of Engineering and Technology, 2018)
The country faces a tremendous growth in the electronics industry along with a exponential growth of electronic waste (e-waste). As volume of e-waste continues to grow, the recycling of electronics becomes more important as it sets the stage for the growth of such recycling industries. An upward flow of electronic waste has been reached in recent years due to the enormous growth in the consumer electronics. E-wastes cannot be considered as trash, they are considered as hazards to environment and health. But these e-wastes in return on recycling offer some valuable resources such as noble metals (Copper, Gold, Silver, Lead etc.). The business opportunities which are available through the metals recovery and the methods for better improvement in waste management were the main theme of this study. This work also analyses the role of divergent shareholders and regulatory enrolled in those trade opportunities. A comparison of the state of art of e-waste management in India with the global practices has been performed in order to study the improvement and challenges.Â